A new agenda for forest conservation and poverty alleviation: making markets work for low-income producers - Scherr, Sara J.; White, A.; Kaimowitz, D. (Forest Trends and CIFOR, 2004)
Community based forestry has the potential to contribute much more to achieving sustainable development and poverty reduction than is the case today. This paper describes and analyzes these potentials and demonstrates their feasibility with real world cases of community forest businesses and innovative policies and business partnerships. This preliminary assessment is offered as a first step in a longer-term effort to understand existing forest product and service markets, and to identify the most promising market opportunities for local community producers, focusing particularly on developing countries. Part I presents the broader context of forestry’s changing relation to rural development and poverty reduction. Part II develops a framework for considering which market niches have potential for poor producers. Part III proposes strategies and targeted actions to realize that potential.